Legal Characteristics of Patents as Collateral Assets in Banking Transactions - Habibah Rizqo; Dyah Ochtorina Susanti; Ainul Azizah (Rechtenstudent, 2026)
Patents as part of intellectual property possess economic value that can potentially be utilized as collateral in banking financing. The development of Indonesian positive law has normatively recognized patents as fiduciary collateral, particularly following amendments to patent legislation and the enactment of creative economy regulations. Nevertheless, in banking practice, patents have not yet been fully accepted as loan collateral due to various juridical and technical constraints. This article aims to analyze the legal characteristics of patents as objects of fiduciary security, examine their regulation based on the principle of legal certainty, and propose future regulatory directions to enable the effective operationalization of patents as loan collateral. This research employs normative legal research methods using statutory and conceptual approaches. The findings indicate that although patents normatively qualify as fiduciary collateral, the absence of valuation standards, execution mechanisms, and integrated registration systems results in insufficient legal certainty. Therefore, comprehensive implementing regulations and an integrated legal framework are required to optimize patents as banking collateral instruments.